Prevalence of dental caries and associated risk factors among adult outpatients attending Gakoma district hospital, Rwanda - HITIMANA, Eugene; Ndayisenga, Leonard (Journal of Orofacial Research, 2022)
Introduction: Dental caries and other oral health conditions are public health challenges worldwide. The World health organization reports the burden of oral diseases to be less in developing countries including Africa and higher in the developed world. Despite health sector improvement in Rwanda after the Genocide against the Tutsi, dental caries has remained among the leading causes of consultation at all levels of the health care delivery pyramid with high numbers in rural communities. The prevalence of dental caries experienced in Rwanda is found to be 64.9% but few studies have been conducted assessing the predisposing risk factors, especially in adults. The objectives of the study included the determination of dental caries prevalence and associated risk factors among adult outpatients who attended Gakoma district hospital in Gisagara district of Rwanda from November 2016 to January 2017. Methods:  Hospital-based cross-sectional study using quantitative methods with a sample size of 281participants aged 18 and above systematically selected randomly from patients who attended Gakoma district hospital’s outpatient department during the study period. The sample size calculation used Yamane’s formula. Ethical approval was gotten from the school of health sciences of Mount Kenya University and informed consents were signed by participants with the right to withdraw at any time without prior justifications. Data collection instruments included a self-administered questionnaire with a close-ended questionnaire on oral health risk factors and a data sheet to extract data from patients’ files after a physical dental examination of study participants. The study collected information on risk factors for dental caries development that included age, gender, oral hygiene practice, alcohol consumption, sugary snacks, and beverages consumption, and tobacco use. Data were analyzed using a statistical package of social sciences at a 95% confidence interval.Results: The prevalence of dental caries is 71.5% among patients attending the outpatient department and predisposing risk factors were found to be old age, gender, poor oral hygiene, consumption of sugary snacks and beverages. Alcohol was also found to contribute to dental caries development, but no statistical significance was found.Conclusions: The prevalence of dental caries was found to be high in the study population and the multifactorial risk factors associated with its development were found to be poor oral hygiene, frequent consumption of sugary snacks and beverages, gender, and old age. The study recommended further studies to explore these multifactorial risk factors on a larger scale.